Revitalization of T-Garden Little Bali in Medan as Education and Recreation Based Tourism Object in Deli Serdang Regency - Yeny Salkina; Dwi Lindarto Hadinugroho (International Journal of Architecture and Urbanism, 2021)
The tourist area of Little Bali T-Garden in Medan is located in Jati Kesuma Village, Kec. Namorambe, Deli Serdang Regency, North Sumatra. Which is one of the natural tourist areas located on the edge of Medan City. The place has an area of ​​± 20 hectares dominated by green open space. This research focuses on knowledge in utilizing existing potential to have a positive impact. The purpose of this research is to revitalize the tourist area to make it more vibrant and useful. This research was conducted using qualitative methods, namely making direct observations in the research area. The phenomenon that occurs in tourist areas has an irregular arrangement and does not fully utilize the land area. The circumstances that occur are things that considered as potentially not being used. Area revitalization uses Place Attachment theory as a basis, outdoor space design theory as a determinant of the needs of tourist areas, and Kevin Lynch's theory will be used to determine what is considered attractive and has the potential to be developed or removed. These results were obtained from the revitalization of the area as an educational and recreational tourism object in Deli Serdang Regency.